PENGEMBANGAN PERENCANAAN PULANG MODEL LIMA - Eka Yulia Fitri; Herliawati; Dian Wahyuni (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Discharge planning is a routine activity in the health care system. However, the implementation of discharge planning has not been done optimally. Generally, implementation of discharge planning in the hospital only as patient’s resume records and lack of information about the patient’s control schedule, medications, and diet after the patient is discharge from the hospital. Effective implementation of discharge planning is expected to reduce the negative impact of health conditions that require continuous care and can increase patient and family satisfaction with health care delivery system. The aims of this study was to determine the effect of the development of LIMA discharge planning model on the implementation of discharge planning carried out by nurses.The study design was a quasi-experiment which aims to develop and test effectivenesss of the LIMA discharge planning model. The sample in this study were 24 nurses at Hospital X in Palembang. The instrument used in this study was developed based on literatures and journal review. Data were analyzed using paired t-test to assess the knowledge of nurses and Wilcoxon test to assess the implementation of discharge planning conducted by nurses with a level of significance of 95% (alpha = 0.05).There was a significant effect on the LIMA discharge planning model on the implementation of discharge planning carried out by nurses at Hospital X Palembang. The LIMA discharge planning model can help nurses in making plan of discharges for patients and families so that the implementation of discharge planning can be conducted in accordance with the standards and can ensure continuity of care for patients after being discharge.